Differences between the strength of preference-performance coupling in two rice stemborers (Lepidoptera: Pyralidae, Crambidae) promotes coexistence at field-plot scales - Horgan, Finbarr G.; Romena, Angelita M.; Bernal, Carmencita C.; Almazan, Maria Liberty P.; Ramal, Angelee Fame (Oxford University Press, 2021)
Two stem-boring moths, the yellow stemborer (YSB) Scirpophaga incertulas (Walker), and the striped stemborer (SSB), Chilo suppressalis (Walker), damage rice in Asia. YSB is the dominant species in much of tropical Asia. Both species are oligophagous on domesticated and wild rice. We investigated the roles of host plant preferences and larval performance in determining the larval densities of both species in rice plots. In screenhouse experiments, YSB showed significant preference–performance coupling. Adults preferred high-tillering rice varieties during early vegetative growth. In contrast, SSB did not demonstrate oviposition preferences under the same screenhouse conditions, but did oviposit less on the wild rice Oryza rufipogon Griff. than on domesticated rice varieties during a choice experiment. Despite differences in preference–performance coupling, larval survival and biomass across 10 varieties were correlated between the two species. YSB and SSB larvae occurred in relatively high numbers on rice varieties with large tillers (IR70, IR68, and T16) in wet and dry season field experiments. However, whereas YSB was the dominant species on IR68 and IR70, it was relatively less abundant on T16, where SSB dominated. Results suggest that YSB preferentially attacked fast-growing rice varieties with high tiller numbers early in the crop cycle. Meanwhile SSB, which has weak preference–performance coupling, occurred in rice plants with large tillers that were relatively free of YSB later in the crop cycle. These factors may allow the species to coexist. We discuss the implications of proximate and ultimate factors influencing stemborer co-occurrence for the sustainable production of rice in tropical Asia.